Conceptualising and maintaining partnership engagement, what is required? An analysis of three third-party policing partnerships in Australia and the UK - van Felius, Margo (International journal of police science & management, 2025)
Third-party policing (TPP) partnerships provide police agencies with an opportunity to address underlying social issues, and allow for longer-term solutions to crime and the development of innovative crime-reduction strategies. A review of the multi-agency policing partnership literature identifies a range of formal and informal factors that impact on implementation and partnership engagement. However, the literature is limited in terms of how and why these factors facilitate or inhibit implementation, and/or how these factors interact. This article applies an international case study methodology involving 55 semi-structured interviews with police officers and representatives from partner agencies across three TPP partnerships, two in Queensland, Australia and one in the United Kingdom. The key findings highlight a range of factors that are important. Five of these are imperative to the successful implementation and sustainability of TPP partnerships and continued partner engagement: (a) clear and shared aims and objectives for the partnership; (b) commitment from management and all involved to partnership working and adequate resourcing; (c) trust, respect and open communication between the partners; (d) information-sharing protocols; and (e) measuring the performance of the partnership. This article further shows that these factors are interdependent and should be considered in the context of the others.